Validating the effectiveness of game-based learning approach in the form of video game for assessing computational thinking - Joo, Tan Meng; Seng, Wong Yoke (Journal of ICT in Education, 2021)
This research aims to validate the effectiveness of students’ understanding in four aspects of computational thinking with the game-based learning assessment. The four aspects of computational thinking involved in this research are decomposition, pattern recognition, abstraction, and algorithm. This research will use a mixed method design approach with a quasi-experiment using a pre-test and post-test nonequivalent group design. The quasi-experiment will validate the effectiveness of students’ understanding on the decomposition, pattern recognition, abstraction, and algorithm aspects of computational thinking with the game-based learning assessment. The qualitative data gathered will be analyzed using thematic analysis. It is expected that the students’ understanding in four aspects of computational thinking with the game-based learning assessment will vary in terms of the effectiveness.